Faster oxygen uptake kinetics during recovery is related to better repeated sprinting ability - Dupont, G.; McCall, A.; Prieur, F.; Millet, G. P.; Berthoin, S. (European Journal of Applied Physiology, 2010)
This study was designed to test the hypothesis that subjects having faster oxygen uptake (VO2) kinetics during off-transients to exercises of severe intensity would obtain the smallest decrement score during a repeated sprint test. Twelve male soccer players completed a graded test, two severe-intensity exercises, followed by 6 min of passive recovery, and a repeated sprint test, consisting of seven 30-m sprints alternating with 20 s of active recovery. The relative decrease in score during the repeated sprint test was positively correlated with time constants of the primary phase for the VO2 off-kinetics (r = 0.85; p < 0.001) and negatively correlated with the VO2 peak (r = -0.83; p < 0.001). These results strengthen the link found between VO2 kinetics and the ability to maintain sprint performance during repeated sprints.